Catalytic upgrading of coal gaseous tar over Y-type zeolites. (15th September 2016) - Kong, Xiaojun; Bai, Yonghui; Yan, Lunjing; Li, Fan
Highlights: Three USY zeolites were evaluated in the upgrading of coal gaseous tar by Py-GC/MS. Excellent cracking ability for condensed aromatics was observed with high yields of BTEXN. Catalyst acidity and coal property were important factors affecting final results. A mechanism was proposed to explain the catalytic cracking over USY zeolites. Abstract: The influence of three ultra-stable Y-type (USY) zeolites with different acidity on the yield of aromatic hydrocarbons such as benzene, toluene, ethyl benzene, xylene, and naphthalene (BTEXN) in coal gaseous tar from coal pyrolysis, especially poly aromatic hydrocarbons (PAHs), have been investigated online by Py-GC/MS. The results indicate that USY zeolites have high catalytic activity for light aromatics formation and condensed aromatics cracking. After the catalytic cracking of USY1 zeolite, the total yield of BTEXN in a long flame coal gaseous tar increases to 3.8 wt%, which is 1.0 wt% for raw coal pyrolysis, and the cracking ratio of PAHs reaches about 23.7%. The total yield of BTEXN in a coking coal gaseous tar increase to 4.0 wt%, 4.4 wt% and 4.3 wt% after catalytic cracking by three USY zeolites (1.5 wt% for raw coal pyrolysis), and the cracking ratio of PAHs are 32.8%, 23.2%, and 27.1%, respectively. Suitable strength and concentration of acid sites are beneficial for the formation of light aromatics. The raw coal property also significantly influences the catalytic effect of USY zeolites. With increasing acidity of the USY zeolites, the catalytic activity to the formation of light aromatics for coal A decreases, while the catalytic activity for coal B increases.